Sikap Peduli Siswa Terhadap Pengurusan Jenazah Pada Sekolah Menengah Atas di Bandung - Elvi Apriani Elvi; Ida Farida (Program Pascasarjana IAIN Langsa, 2021)
Abstrack: This study aims to determine student’sattitudes about the managementfor corpses. This study uses a quantitative approach, the instrumentused refers to 3 indicators of student attitudes in the form of guidelines using a questionnaire.Retrieval of data using google form distributed to 31 class X students in a high school inthe city of Bandung.The method used is descriptive correlational. Based on the results of the study, it was concludedthat there was an increase apathetic studen’t attitudes about the management of corpses.